Pharmacy Management System (PhaMSys)/ Norfatin Liyana Yussof - Yussof, Norfatin Liyana (2016)
Pharmacy Management System (PhaMSys) is a system that has been developed to manage the medication management in Bestari Pharmacy. There are many problems that faced by pharmacy in order to manage the medication. To reduce the problems, PhaMSys has been developed for Bestari Pharmacy. PhaMSys is made for user in Bestari Pharmacy, which are Admin, Pharmacist and Staff to manage the medication management. Rapid Application Model is used as a methodology in developing the PhaMSys since this project is adapted from the previous project that has similar studies. Once the development of PhaMSys is success, the evaluation has been conducted. This evaluation has been conducted by three experts and user. The questions consist of six constructs to the experts included in term of interface, usability, efficiency, ease of use, satisfaction and user experience to get the suggestions and comments. The result shows that the most of experts agreed that the PhaMSys is easy to use. The users’ evaluation involved 30 potential users. They evaluated by six constructs of questions. Six constructs of questions which are ease of use, efficiency, interface, usability, user experience and satisfaction. The result has been showed that the respondents agreed that item of the efficiency in PhaMSys were well integrated with the highest mean 4.23 (SD = 0.5274).